A rosin-based nanocomposite plugging agent and its preparation method and application
By preparing rosin-based nanocomposite sealant with core-shell-crown structure, the shortcomings of inorganic-organic composite sealant in water dispersion stability and high temperature stability are solved, and high-efficiency sealing and environmental protection performance are improved.
Patent Information
- Application Number
- CN202311458856.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-03
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-11-03
AI Technical Summary
The existing inorganic-organic composite sealing agents have shortcomings in water dispersion stability and high temperature stability, and the use of synthetic resins has caused environmental problems.
A rosin-based nanocomposite sealant with a core-shell-crown structure was prepared by semi-continuous emulsion polymerization method. Nanosilica modified with silane coupling agent was used as the core, a modified rosin resin as the shell layer, and a hydrophilic crosslinking layer as the canopy layer, which improved colloid dispersion stability and high-temperature adaptive sealing ability.
It realizes efficient sealing on the nano-micron scale, strengthens the adaptive sealing ability at high temperatures, and improves the biodegradability and environmental protection of the sealing agent by introducing natural rosin components.
Smart Images

Figure CN117511523B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of drilling fluid plugging and anti-collapse materials, in particular to a preparation method and application of a rosin-based nano-composite plugging agent. Background Art
[0002] In recent years, oil and gas exploration and development have gradually developed towards unconventional areas. Unconventional oil and gas layers have complex geological structures, strong heterogeneity, and generally develop nano-micron pore throats and micro-cracks. Conventional drilling fluid plugging agents are difficult to effectively plug them, which can easily cause wellbore instability and restrict the smooth progress of exploration and development. Research and development of nano-micron scale drilling fluid plugging agents and strengthening the plugging of drilling fluids on micropores and cracks are one of the key technologies to solve the problem of wellbore instability. At present, a variety of inorganic, organic and inorganic-organic nano-composite plugging materials have been developed. Among them, inorganic-organic composite materials have both the high strength and thermal stability of inorganic materials and the flexibility and processability of organic materials. They are the research hotspots of high-performance micro-nano plugging agents in recent years. In addition, by controlling the synthesis steps, core-shell structure and components, inorganic-organic composite materials can further improve their comprehensive performance to cope with complex downhole environments. However, inorganic-organic composite materials currently use synthetic resins as coating structures. In the long run, these materials will bring environmental problems that cannot be ignored; in addition, the water dispersion stability and high temperature stability of inorganic-organic composite materials are still facing challenges. Therefore, it is crucial to develop high-performance environmentally friendly drilling fluid plugging materials using renewable and biodegradable raw materials, and it is also necessary to improve the water dispersion stability and high temperature stability of inorganic-organic composites. Summary of the invention
[0003] Aiming at the problem that the existing inorganic-organic composite plugging agent has poor water dispersion stability and high temperature stability, the present invention provides a rosin-based nano-composite plugging agent for water-based drilling fluid and a preparation method thereof.
[0004] The plugging agent is a nano-composite particle with a core-shell-crown structure prepared by a semi-continuous emulsion polymerization method. It has excellent colloidal dispersion stability and can form efficient plugging at the nanometer scale. The plugging agent can undergo thermal deformation at high temperatures to enhance the adaptive plugging ability at high temperatures. At the same time, the plugging agent introduces a natural rosin component, is easily biodegradable, and has good environmental protection.
[0005] The rosin-based nanocomposite plugging agent provided by the invention is a nanocomposite particle with a core-shell-crown composite structure, wherein nano silicon dioxide modified by a silane coupling agent is used as the core; the surface of the core is coated with a shell layer, and the surface of the shell layer is coated with a crown layer.
[0006] The shell layer is made of a material having a molecular structure shown in formula (1);
[0007]
[0008] In formula (1), the molar ratio of x to y is 1:(0.1-0.6), preferably 1:0.25.
[0009] The canopy is made of a material having a molecular structure shown in formula (2);
[0010]
[0011] In formula (2), the molar ratio of a, b and c is (0.005-0.05):(0.1-1):1, preferably 0.07:0.4:1.
[0012] The shell layer is made of a polymer of a modified rosin monomer and a hydrophobic monomer, styrene; the modified rosin monomer is dehydroabietic acid methacrylate represented by formula (3):
[0013]
[0014] The canopy is made of a polymer of a hydrophilic monomer and a crosslinking monomer. The hydrophilic monomers are 2-acrylamide-2-methylpropanesulfonic acid and N,N-dimethylacrylamide. The molar ratio of 2-acrylamide-2-methylpropanesulfonic acid to N,N-dimethylacrylamide is (0.1-1):1, preferably 0.4:1. The crosslinking monomer is N,N'-methylenebisacrylamide, and its molar amount is 1%-5% of the total molar amount of the two hydrophilic monomers, preferably 5%.
[0015] The present invention also provides a method for preparing a rosin-based nanocomposite plugging agent, the steps of which are as follows:
[0016] S1. Preparation of silane coupling agent modified nano-silica:
[0017] The nano-silicon dioxide was ultrasonically dispersed in anhydrous ethanol, and then the pre-hydrolyzed silane coupling agent was added dropwise to the nano-silicon dioxide anhydrous ethanol dispersion, and the temperature was raised to 85°C, and nitrogen was refluxed for 5 hours. After the reaction, the nano-silicon dioxide modified by the silane coupling agent was obtained by centrifugation, washing, and drying. The surface was modified by the silane coupling agent containing a double bond structure to form a polymerizable core structure, which provided conditions for the subsequent surface grafting reaction with other monomers.
[0018] S2, preparing a shell layer coated with modified nano-silicon dioxide;
[0019] The emulsifier and the pH buffer sodium bicarbonate are dissolved in deionized water to obtain an emulsifier solution; the modified nano-silicon dioxide prepared in step S1 is ultrasonically dispersed in a mixed solution of modified rosin monomer and hydrophobic monomer styrene, and then the mixed solution is added to the emulsifier solution, and pre-emulsified for 30 minutes with high-speed stirring, and then the temperature is raised to 80-82° C., an initiator is added, and nitrogen is passed through the reaction for 1 hour to obtain an emulsion containing a core-shell structure of modified rosin resin encapsulating modified nano-silicon dioxide.
[0020] S3, preparing a hydrophilic cross-linked canopy;
[0021] 2-Acrylamide-2-methylpropanesulfonic acid, N,N-dimethylacrylamide and N,N'-methylenebisacrylamide are dissolved in deionized water, and the pH is adjusted to be neutral to obtain a mixed hydrophilic monomer solution; the mixed hydrophilic monomer solution is continuously dripped into the core-shell structure emulsion obtained in step S2, and after the dripping is completed, a total reaction system is obtained; the temperature is raised to 90° C. and the total reaction system is aged for 1 hour, and then the temperature is lowered and filtered to obtain a rosin-based nano-composite plugging agent for water-based drilling fluid.
[0022] The nano composite plugging agent of the present invention has a particle size distribution of 60-120 nm, has good dispersibility in water-based drilling fluid, can effectively plug nanometer and micrometer pores, and improves the stability of the well wall.
[0023] Preferably, in step S1, the silane coupling agent is 3-(isobutylene acyloxy)propyltrimethoxysilane, and the silane coupling agent is added to a mixture of ethanol and water (ethanol to water volume ratio 100:1), and pre-hydrolyzed for 30 minutes at pH = 4. The average particle size of the nano-silicon dioxide is 30nm. The mass ratio of the silane coupling agent to the nano-silicon dioxide is 0.4:1; the concentration of the nano-silicon dioxide in anhydrous ethanol is 0.1g / mL.
[0024] Preferably, in step S2, the emulsifier is a composition of sodium dodecyl sulfate and Triton X100 in a mass ratio of (3-5): 1. Further preferably, the mass ratio of sodium dodecyl sulfate to Triton X100 is 4: 1. The mass ratio of the modified rosin monomer to styrene is 1: (0.4-2.3), preferably 1: 1. The initiator is ammonium persulfate or potassium persulfate.
[0025] Preferably, in step S3, the mixed hydrophilic monomer solution is continuously dripped into the core-shell structure emulsion obtained in step S2, and the continuous dripping conditions are: temperature 80-82° C., and continuous dripping time 0.5-1 h.
[0026] In the overall reaction system of step S3, the ratio of the mass of modified nano-silica to the mass of hydrophobic monomer is (0.01-0.07):1, preferably 0.03:1. The ratio of the total mass of hydrophilic monomer and cross-linking monomer to the total mass of modified rosin monomer and hydrophobic monomer is (0.1-0.3):1, preferably 0.2:1. The mass of the initiator is 0.8%-1.2% of the total monomer mass (the total mass of modified rosin monomer, styrene, and hydrophilic monomer), preferably 1%; the ratio of the mass of the emulsifier to the mass of the hydrophobic monomer is (0.04-0.06):1, preferably 0.05:1; the molar ratio of the pH buffer and the initiator is 1.5:1; the total solid content of the system is 20wt%.
[0027] The rosin-based nano-composite plugging agent is suitable for water-based drilling fluid, and the content of the rosin-based nano-composite plugging agent in the water-based drilling fluid is 2-4wt%.
[0028] Compared with the prior art, the present invention is beneficial in that:
[0029] (1) The present invention ensures the smooth progress of the reaction through a semi-continuous feeding method, and finally forms a nano-composite plugging agent with nano-silicon dioxide as the "core" structure, modified rosin resin as the "shell" structure, and a hydrophilic cross-linked layer as the "crown" structure. Its hydrophilic crown structure can improve the colloidal dispersion stability of the plugging agent, maintain the nano-micron dispersion in the water-based drilling fluid, and at the same time, with the help of the bridging effect of the rigid core and the thermal deformation effect of the modified rosin resin shell layer, it can form a better plugging effect on micro-nano pores and cracks and enhance the high-temperature adaptive plugging performance.
[0030] (2) The nanocomposite plugging agent of the present invention introduces a natural rosin component, which, on the one hand, enables the plugging agent to have the thermal deformation ability of rosin resin and improves its thermal deformation temperature through styrene copolymerization. On the other hand, the natural rosin component is connected to the resin main chain through an ester bond, which improves the biodegradability of the product and ensures the environmental protection of the plugging agent. In addition, the rosin-based nanocomposite plugging agent of the present invention applies rosin to a water-based drilling fluid system, expands the application range of rosin materials, and has good application prospects.
[0031] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is an infrared spectrum of the rosin-based nanocomposite plugging agent for water-based drilling fluid prepared in Example 1 of the present invention.
[0033] Figure 2 This is a transmission electron microscope image of the rosin-based nanocomposite plugging agent for water-based drilling fluid prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0035] Example 1
[0036] A preparation method of a rosin-based nanocomposite plugging agent for water-based drilling fluid comprises the following steps:
[0037] S1. Preparation of silane coupling agent modified nano-silica
[0038] Take 1g of nano-silica and add it to 10mL of anhydrous ethanol, and ultrasonically disperse it for 15min; add 3-(isobutyleneoxy)propyltrimethoxysilane (0.4g) pre-hydrolyzed for 30min under pH 4 conditions dropwise to the nano-silica ethanol dispersion, and the mixed solution is heated to 85°C and refluxed with nitrogen for 5h. After the reaction is completed, it is centrifuged at 8000rpm, and the product is washed with anhydrous ethanol. After drying at 55°C, nano-silica modified with a silane coupling agent is obtained.
[0039] S2. Preparation of modified rosin resin coating shell layer
[0040] 0.4g of sodium dodecyl sulfate, 0.1g of Triton X100 and 0.0663g of sodium bicarbonate were dissolved in 38g of deionized water to obtain an emulsifier solution; 0.3g of nano-silica modified by a silane coupling agent was added to a hydrophobic monomer mixture of 5g of dehydroabietic acid methacrylate and 5g of styrene, and ultrasonically dispersed for 10min; the mixed hydrophobic monomer solution was added to the emulsifier solution, stirred at 1000rpm for pre-emulsification for 30min, then heated to 80°C, 0.12g of ammonium persulfate (dissolved in 5g of deionized water) was added dropwise, and nitrogen was passed through the reaction for 1h to obtain an emulsion containing a core-shell structure coated with a modified rosin resin.
[0041] S3. Preparation of hydrophilic cross-linked canopy
[0042] 0.9452 g of 2-acrylamide-2-methylpropanesulfonic acid, 1.0548 g of N,N-dimethylacrylamide, and 0.1172 g of N,N'-methylenebisacrylamide were dissolved in 5 g of deionized water, and the mixed hydrophilic monomer solution was continuously dripped into the core-shell structure emulsion obtained in step S2 after adjusting the pH to neutral, and the dripping was continued at 80°C for 1 hour; after the dripping was completed, the temperature was raised to 90°C and the reaction system was matured for 1 hour, and then the temperature was lowered and passed through a 200-mesh sieve to obtain a rosin-based nano-composite plugging agent for water-based drilling fluid.
[0043] Example 2
[0044] A preparation method of a rosin-based nanocomposite plugging agent for water-based drilling fluid, wherein steps S1 and S2 are the same as those in Example 1, and step S3 is as follows:
[0045] 0.1885 g of 2-acrylamide-2-methylpropanesulfonic acid, 0.8115 g of N,N-dimethylacrylamide and 0.014 g of N,N'-methylenebisacrylamide were dissolved in 5 g of deionized water, and the mixed hydrophilic monomer solution was continuously dripped into the core-shell structure emulsion after adjusting the pH to neutral, and the dripping was continued at 80°C for 1 hour; after the dripping was completed, the temperature was raised to 90°C and the reaction system was matured for 1 hour, and then the temperature was lowered and passed through a 200-mesh sieve to obtain a rosin-based nano-composite plugging agent for water-based drilling fluid.
[0046] Example 3
[0047] Preparation of a rosin-based nanocomposite plugging agent for water-based drilling fluid, step S1 is the same as in Example 1, and steps S2 and S3 are as follows:
[0048] S2. Preparation of modified rosin resin coating shell layer
[0049] 0.4 g of sodium dodecyl sulfate, 0.1 g of Triton X100, and 0.0718 g of sodium bicarbonate were dissolved in 42 g of deionized water, and 0.3 g of nano-silica modified by a silane coupling agent was added to a hydrophobic monomer mixture of 5 g of dehydroabietic acid methacrylate and 5 g of styrene. After ultrasonic dispersion for 10 min, the mixed hydrophobic monomers were added to the emulsifier solution, stirred for pre-emulsification at 1000 rpm for 30 min, then heated to 82 ° C, 0.13 g of ammonium persulfate (dissolved in 5 g of deionized water) was added dropwise, and nitrogen was passed through the reaction for 1 h to obtain a core-shell structure coated with a modified rosin resin.
[0050] S3. Preparation of hydrophilic cross-linked canopy
[0051] 2.0292 g of 2-acrylamide-2-methylpropanesulfonic acid, 0.9708 g of N,N-dimethylacrylamide and 0.0906 g of N,N'-methylenebisacrylamide were dissolved in 5 g of deionized water, and the mixed hydrophilic monomer solution was continuously dripped into the core-shell structure emulsion after adjusting the pH to neutral, and the dripping was continued at 82°C for 0.5 h. After the dripping was completed, the temperature was raised to 90°C and the reaction system was matured for 1 h, and then the temperature was lowered and passed through a 200-mesh sieve to obtain a rosin-based nano-composite plugging agent for water-based drilling fluid.
[0052] Example 4
[0053] Preparation of a rosin-based nanocomposite plugging agent for water-based drilling fluid, step S1 is the same as in Example 1, and steps S2 and S3 are as follows:
[0054] S2. Preparation of modified rosin resin coating shell layer
[0055] 0.5 g of sodium dodecyl sulfate, 0.1 g of Triton X100, and 0.0486 g of sodium bicarbonate were dissolved in 34 g of deionized water, and 0.3 g of nano-silica modified by a silane coupling agent was added to a hydrophobic monomer mixture of 7 g of dehydroabietic acid methacrylate and 3 g of styrene. After ultrasonic dispersion for 10 min, the mixed hydrophobic monomers were added to the emulsifier solution, stirred for pre-emulsification at 1000 rpm for 30 min, then heated to 82 ° C, 0.088 g of potassium persulfate (dissolved in 5 g of deionized water) was added dropwise, and nitrogen was passed through the reaction for 1 h to obtain a core-shell structure coated with a modified rosin resin.
[0056] S3. Preparation of hydrophilic cross-linked canopy
[0057] 0.1885 g of 2-acrylamide-2-methylpropanesulfonic acid, 0.8115 g of N,N-dimethylacrylamide and 0.0701 g of N,N'-methylenebisacrylamide were dissolved in 5 g of deionized water, and the mixed hydrophilic monomer solution was continuously dripped into the core-shell structure emulsion after adjusting the pH to neutral, and the dripping was continued at 82°C for 0.5 h. After the dripping was completed, the temperature was raised to 90°C and the reaction system was matured for 1 h, and then the temperature was lowered and passed through a 200-mesh sieve to obtain a rosin-based nano-composite plugging agent for water-based drilling fluid.
[0058] Example 5
[0059] Preparation of a rosin-based nanocomposite plugging agent for water-based drilling fluid, step S1 is the same as in Example 1, and steps S2 and S3 are as follows:
[0060] S2. Preparation of modified rosin resin coating shell layer
[0061] 0.3 g of sodium dodecyl sulfate, 0.1 g of Triton X100, and 0.0861 g of sodium bicarbonate were dissolved in 42 g of deionized water, and 0.3 g of nano-silica modified by a silane coupling agent was added to a hydrophobic monomer mixture of 3 g of dehydroabietic acid methacrylate and 7 g of styrene. After ultrasonic dispersion for 10 min, the mixed hydrophobic monomers were added to the emulsifier solution, stirred for pre-emulsification at 1000 rpm for 30 min, then heated to 80° C., 0.156 g of potassium persulfate (dissolved in 5 g of deionized water) was added dropwise, and nitrogen was passed through the reaction for 1 h to obtain a core-shell structure coated with a modified rosin resin.
[0062] S3. Preparation of hydrophilic cross-linked canopy
[0063] 2.0292 g of 2-acrylamide-2-methylpropanesulfonic acid, 0.9708 g of N,N-dimethylacrylamide, and 0.0302 g of N,N'-methylenebisacrylamide were dissolved in 5 g of deionized water. After adjusting the pH to neutral, the mixed hydrophilic monomer solution was continuously dripped into the core-shell structure emulsion at 80°C for 0.5 h. After the dripping was completed, the temperature was raised to 90°C and the reaction system was matured for 1 h. Subsequently, the temperature was lowered and passed through a 200-mesh sieve to obtain a rosin-based nano-composite plugging agent for water-based drilling fluid.
[0064] Comparative Example 1
[0065] On the basis of Example 1, step S3 is removed to directly prepare a core-shell structure emulsion coated with modified rosin resin as a plugging agent. The preparation method is as follows:
[0066] (1) Preparation of silane coupling agent modified nano-silica
[0067] Take 1g of nano-silica and add it to 10mL of anhydrous ethanol, and ultrasonically disperse it for 15min; add 3-(isobutyleneoxy)propyltrimethoxysilane (0.4g) pre-hydrolyzed for 30min under pH 4 conditions dropwise to the nano-silica ethanol dispersion, and the mixed solution is heated to 85°C and refluxed with nitrogen for 5h. After the reaction is completed, it is centrifuged at 8000rpm, and the product is washed with anhydrous ethanol. After drying at 55°C, nano-silica modified with a silane coupling agent is obtained.
[0068] (2) Preparation of modified rosin resin coating shell
[0069] 0.4g of sodium dodecyl sulfate, 0.1g of Triton X100 and 0.0663g of sodium bicarbonate were dissolved in 38g of deionized water to obtain an emulsifier solution; 0.3g of nano-silica modified by a silane coupling agent was added to a hydrophobic monomer mixture of 5g of dehydroabietic acid methacrylate and 5g of styrene, and ultrasonically dispersed for 10min; the mixed hydrophobic monomer solution was added to the emulsifier solution, stirred at 1000rpm for pre-emulsification for 30min, then heated to 80°C, 0.12g of ammonium persulfate (dissolved in 5g of deionized water) was added dropwise, and nitrogen was passed through the reaction for 1h to obtain a core-shell structure emulsion coated with a modified rosin resin.
[0070] Performance Testing:
[0071] 1. Physical and chemical properties test
[0072] (1) Monomer conversion rate
[0073] The monomer conversion rate of the product was tested by gravimetric method. A small amount of the product of the example was placed on aluminum foil, 2 drops of 1% hydroquinone ethanol solution were added to prevent the polymerization of unpolymerized monomers, and the mixture was dried at 140° C. to constant weight. The monomer conversion rate (C%) was calculated as follows:
[0074]
[0075] In the formula, m 0 、m 1 and m 2 are the mass of aluminum foil, the total mass of plugging agent and aluminum foil before drying, and the total mass of plugging agent and aluminum foil after drying, g; m 3 、m 4 、m T and m a They are the total mass of monomers, the total mass of non-volatile matter, the total mass of the reaction system and the mass of condensates, g.
[0076] (2) Polymer coverage
[0077] The Soxhlet extraction method was used to test the coverage of the modified rosin resin shell layer on the surface of nano-silica in each embodiment. A small amount of plugging agent sample was taken, wrapped with a 100nm filter membrane, placed in a Soxhlet extractor, and acetone was used as the extractant. After 24 hours of extraction, the grafting coverage of the resin shell layer on the surface of nano-silica was calculated based on the mass difference before and after extraction.
[0078] Similarly, the coating grafting rate of the hydrophilic corona on the core-shell structure was tested, the solvent was deionized water, and the cleaning condition was 60℃ / 24h. According to the mass difference before and after cleaning, the coating rate of the hydrophilic corona relative to the nano-silica and the coated modified rosin resin layer was calculated.
[0079] (3) Particle size distribution
[0080] The samples of each embodiment and the sample of comparative example 1 were respectively prepared into a water dispersion with a concentration of 0.1 wt%, and the average particle size of each sample before and after centrifugation at 6000 rpm / 20 min was measured using a dynamic light scattering instrument. In addition, the sample was dried to obtain a solid product, and then the water dispersion was re-prepared to test the redispersed particle size of each sample.
[0081] The test results of the physical and chemical properties of the rosin-based nanocomposite plugging agents for water-based drilling fluids prepared in Examples 1-5 and the modified rosin resin core-shell structure emulsion prepared in Comparative Example 1 are shown in Table 1 below.
[0082] Table 1. Physical and chemical properties test results
[0083]
[0084] It can be seen from the experimental results in Table 1 that the monomer conversion rate (88.65%-98.90%), modified rosin resin shell layer coverage (84.91%-91.76%) and hydrophilic cross-linked canopy layer coverage (82.30%-86.43%) of the rosin-based nanocomposite plugging agent prepared by the present invention are all high, indicating that the hydrophilic and hydrophobic monomers in the plugging agent are successfully copolymerized and converted and the hydrophilic and hydrophobic layers have a clearly structured grafting coating. The average particle size of the rosin-based nanocomposite plugging agent of each embodiment is about 60-120nm, which can effectively match nano-micron-scale pores and form efficient plugging; after centrifugation at 6000rpm / 20min, the average particle size of the plugging agent of the present invention does not change much, indicating that it has excellent long-term dispersion stability; in addition, after the plugging agent of the present invention is dried and dispersed, its average particle size is only slightly increased, showing excellent redispersion ability, which helps the plugging agent of the present invention to be used in emulsion and solid forms. The product of Comparative Example 1 does not contain a hydrophilic canopy structure and has a small initial particle size. Due to the lack of electrostatic repulsion between particles provided by the hydrophilic canopy (which mainly relies on emulsifier dispersion), the dispersion stability is poor, the particle size increases significantly after high-speed centrifugation, and it cannot be dispersed again after drying, which greatly limits its practical application in water-based drilling fluids.
[0085] 2. Structural characterization test
[0086] (1) Infrared spectrum test
[0087] The infrared spectrum of the rosin-based nanocomposite plugging agent prepared in Example 1 was tested using an infrared spectrometer and compared with its precursor nano-silicon dioxide raw material. The results are shown in Figure 1 As shown in the figure, Example 1 at 1110cm -1 The antisymmetric stretching vibration peak of Si-O-Si bond appeared at 1721 cm -1 A strong absorption peak of the ester carbonyl group in the modified rosin monomer appeared at 3025 cm -1 The stretching vibration peak of the benzene ring in styrene appears at 1628 cm -1 and 1543cm -1 The infrared characteristic peak of secondary / tertiary amide appears at 1182cm -1 and 1041cm -1 The infrared characteristic peak of sulfonic acid group appeared at 147°. The infrared spectrum test results showed that the target product had been successfully synthesized.
[0088] (2) Microscopic morphology
[0089] The microscopic morphology of the rosin-based nanocomposite plugging agent prepared in Example 1 was observed using a transmission electron microscope. Figure 2 As shown. Figure 2It can be seen that the rosin-based nanocomposite plugging agent of the present invention has a nano-spherical structure, and the particle size is similar to the test result of the dynamic light scattering method. In addition, the rosin-based nanocomposite plugging agent of the present invention has an obvious core-shell-crown multilayer coating structure, which can give full play to the role of each component.
[0090] 3. Drilling fluid performance test
[0091] Preparation of bentonite-based slurry: 0.64 g of anhydrous sodium carbonate and 16 g of sodium-based bentonite were added to 400 mL of water in sequence, stirred at 8000 rpm for 30 min, and then sealed and cured at room temperature for 24 h;
[0092] Preparation of water-based drilling fluid: Take the cured bentonite-based slurry, add 2 wt % of the plugging agents prepared in Examples 1-5 and Comparative Example 1, and stir for 30 minutes to obtain a water-based drilling fluid test slurry of the plugging agent.
[0093] The rheological filtration properties of the base slurry and each test slurry after aging at 160°C for 16 hours were evaluated according to the method in GB16783.1-2014. The test results are shown in Table 2 below.
[0094] Table 2. Drilling fluid rheological filtration performance test results
[0095]
[0096] As can be seen from Table 2, the rosin-based nanocomposite plugging agent of the present invention has good compatibility with bentonite-based slurry, has the functions of viscosity enhancement, shear enhancement and fluid loss reduction, and can significantly reduce high temperature and high pressure fluid loss, showing better temperature resistance. The product of Comparative Example 1 lacks a hydrophilic canopy structure, has poor dispersibility in drilling fluid, and weak interaction with clay, resulting in poor viscosity enhancement and shear enhancement effects, and almost no ability to reduce API fluid loss; however, due to its thermally deformable modified rosin resin layer, it shows a certain high temperature and high pressure fluid loss reduction effect.
[0097] 4. Micropore plugging performance test
[0098] According to Table 2, the rosin-based nano-composite plugging agent prepared in the above-mentioned Example 1 has the best plugging and filtration loss reduction performance. Therefore, the rosin-based nano-composite plugging agent prepared in the above-mentioned Example 1 was further used as an evaluation object to evaluate the micropore plugging performance. And comparative example 1 was used as a comparative sample to carry out the same experiment. In the experiment, microporous filter membranes of 200nm, 300nm and 400nm were used as filtration loss media to test the micropore filtration loss of the base slurry and each test slurry at room temperature (25°C), medium pressure (0.7MPa) and high temperature (150°C), high pressure (3.5MPa). The test results are shown in Table 3 below.
[0099] Table 3. Micropore plugging performance test results
[0100]
[0101] As can be seen from Table 3, the rosin-based nanocomposite plugging agent prepared by the present invention can significantly improve the micropore plugging ability of the drilling fluid at both room temperature and high temperature and high pressure, and reduce the micropore loss. At room temperature, the plugging agent has nanometer-micrometer scale dispersion in the drilling fluid, and can bridge and fill the fine wrinkles and gaps formed by clay particles to form a dense plugging layer, thereby improving the quality of the mud cake and reducing the micropore loss; at high temperature, the modified rosin resin shell layer of the plugging agent is softened and deformed, and bridged with rigid particles, which promotes a tighter connection between particles, thereby forming a dense hydrophobic plugging barrier, effectively reducing the high temperature and high pressure micropore loss. In addition, the rosin-based nanocomposite plugging agent prepared by the present invention can form an effective plugging for the 200-400nm loss medium, showing adaptive plugging. Due to the lack of a hydrophilic canopy structure, the product of Comparative Example 1 has poor dispersibility and compatibility with the base slurry, making it difficult to maintain nanoscale dispersion and unable to form an effective plugging for the nano-microporous loss medium.
[0102] 5. Environmental performance test
[0103] The ratio method of biological oxygen demand (BOD) to chemical oxygen demand (COD) was used to examine the environmental performance of the rosin-based nanocomposite plugging agent prepared in Example 1. The test results are shown in Table 4.
[0104] It can be seen from Table 4 that the rosin-based nanocomposite plugging agent prepared by the present invention is of the easily biodegradable grade and has excellent environmental performance.
[0105] Table 4. Environmental performance test results
[0106]
[0107]
[0108] In summary, the rosin-based nanocomposite plugging agent for water-based drilling fluid of the present invention has a nano-silicon dioxide rigid core, a modified rosin resin shell layer and a hydrophilic cross-linked crown structure, wherein the hydrophilic layer ensures the nano-micrometer scale colloidal dispersion stability of the plugging agent in the water-based drilling fluid, and the bridging effect of the rigid core and the thermal deformation effect of the modified rosin resin layer strengthen the nano-micrometer adaptive plugging ability of the plugging agent. At the same time, the plugging agent has good compatibility with the drilling fluid and can improve the rheological filtration performance. In addition, the plugging agent introduces a natural rosin component, is easily biodegradable, and is environmentally friendly.
[0109] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A rosin-based nanocomposite plugging agent, characterized in that: The plugging agent is a nanocomposite particle with a core-shell-crown composite structure, wherein nano silicon dioxide modified by a silane coupling agent is used as the core; the surface of the core is coated with a shell layer, and the shell layer is made of a material with a molecular structure shown in formula (1); the surface of the shell layer is coated with a crown layer, and the crown layer is made of a material with a molecular structure shown in formula (2); In formula (1), the molar ratio of x to y is 1:(0.1-0.6); In formula (2), the molar ratio of a, b and c is (0.005-0.05):(0.1-1):
1.
2. The rosin-based nanocomposite plugging agent according to claim 1, characterized in that: The shell layer is made of a polymer of a modified rosin monomer and a hydrophobic monomer, styrene; the molecular structure of the modified rosin monomer is shown in formula (3):
3. The rosin-based nanocomposite plugging agent according to claim 1, characterized in that: The crown layer is made of a polymer of a hydrophilic monomer and a cross-linking monomer; the hydrophilic monomer is 2-acrylamide-2-methylpropanesulfonic acid and N,N-dimethylacrylamide; and the cross-linking monomer is N,N'-methylenebisacrylamide.
4. A method for preparing the rosin-based nanocomposite plugging agent according to any one of claims 1 to 3, characterized in that: Here are the steps: S1. Preparation of silane coupling agent modified nano-silica: The nano-silicon dioxide is ultrasonically dispersed in anhydrous ethanol, and then the pre-hydrolyzed silane coupling agent is added dropwise to the nano-silicon dioxide anhydrous ethanol dispersion, the temperature is raised to 85° C., nitrogen is passed through the reflux reaction for 5 hours, and after the reaction is completed, the nano-silicon dioxide modified by the silane coupling agent is obtained by centrifugation, washing, and drying; S2. Preparation of a shell layer coated with modified nano-silicon dioxide: Dissolving an emulsifier and a pH buffer in deionized water to obtain an emulsifier solution; separately taking the modified nano-silicon dioxide prepared in step S1 and ultrasonically dispersing it in a mixed solution of modified rosin monomer and hydrophobic monomer, then adding the mixed solution to the emulsifier solution, stirring at high speed for pre-emulsification for 30 minutes, then heating to 80-82° C., adding an initiator, and reacting with nitrogen to obtain an emulsion containing a core-shell structure of modified rosin resin encapsulating modified nano-silicon dioxide; S3. Preparation of hydrophilic cross-linked canopy: 2-Acrylamide-2-methylpropanesulfonic acid, N,N-dimethylacrylamide and N,N'-methylenebisacrylamide are dissolved in deionized water, and the pH is adjusted to be neutral to obtain a mixed hydrophilic monomer solution; the mixed hydrophilic monomer solution is continuously dripped into the core-shell structure emulsion obtained in step S2, and after the dripping is completed, a total reaction system is obtained; the temperature is raised to 90° C. and the total reaction system is aged for 1 hour, and then the temperature is lowered and filtered to obtain a rosin-based nano-composite plugging agent for water-based drilling fluid.
5. The method for preparing the rosin-based nanocomposite plugging agent according to claim 4, characterized in that: In step S3, the mixed hydrophilic monomer solution is continuously dripped into the core-shell structure emulsion obtained in step S2, and the continuous dripping conditions are: temperature 80-82° C., and continuous dripping time is 0.5-1 h.
6. The method for preparing the rosin-based nanocomposite plugging agent according to claim 4, characterized in that: The silane coupling agent is 3-(isobutyleneoxy)propyltrimethoxysilane. The silane coupling agent is added into a mixed solution of ethanol and water and pre-hydrolyzed for 30 minutes under the condition of pH=4.
7. The method for preparing the rosin-based nanocomposite plugging agent according to claim 4, characterized in that: In step S2, the emulsifier is a composition of sodium dodecyl sulfate and Triton X100 in a mass ratio of (3-5):
1.
8. The method for preparing the rosin-based nanocomposite plugging agent according to claim 4, characterized in that: In the overall reaction system of step S3, the mass ratio of the modified nano-silica to the hydrophobic monomer is (0.01-0.07):1; the total mass ratio of the hydrophilic monomer and the cross-linking monomer to the total mass ratio of the modified rosin monomer and the hydrophobic monomer is (0.1-0.3):
1.
9. An application of the rosin-based nanocomposite plugging agent as claimed in any one of claims 1 to 3, characterized in that: Used in water-based drilling fluid, the content of rosin-based nano-composite plugging agent in the water-based drilling fluid is 2-4wt%.